Restrictive physiology masked by cardiac tamponade: A rare cooccurrence in a child with lymphoblastic T-cell lymphoma - Atit A Gawalkar; Soumitra Ghosh; Dinakar Bootla; Pruthvi C Revaiah; Charanpreet Singh; Parminder Singh Otaal (Wolters Kluwer Medknow Publications, 2022)
Cardiac involvement in T-cell lymphoma is not uncommon. Pericardial effusion is the most common manifestation of cardiac involvement with restrictive cardiomyopathy (RCM) due to tumor infiltration being extremely rare. The presence of paroxysmal nocturnal dyspnea and orthopnea in a patient presenting with pericardial effusion could be related to tamponade or underlying myocardial disease. Hence, reevaluation after pericardiocentesis is warranted. We describe a 14-year-old boy with advanced T-cell lymphoma presenting with cardiac tamponade. Repeat echocardiography after pericardiocentesis revealed mediastinal mass infiltrating cardiac chambers and great vessels along with features of RCM secondary to tumor infiltration.